Aktualisasi Nilai-Nilai Moderasi dalam Pandangan Islam - Bustomi, Ahmad; Zuhairi, Zuhairi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
This article aimed to explain how Muslims should implement their religion in a moderate manner in order to create a safe and peaceful life. This article is library research by focusing on library discourses which the sources were taken from the journal article, books, and newspapers. According to the analysis, there were several moderate values that Muslims should implement in their life in accordance to establish a peaceful life: Tawasuth which means taking a middle way between right and left extreme; Tawazun which means balance between naqli and aqli, world-oriented and afterworld-oriented; and Tasamuh which means tolerance.